2023
DOI: 10.3390/agriculture14010004
|View full text |Cite
|
Sign up to set email alerts
|

Some Agronomic Properties of Winter Wheat Genotypes Grown at Different Locations in Croatia

Valentina Spanic,
Goran Jukic,
Marina Zoric
et al.

Abstract: A collection of fourteen winter wheat accessions was evaluated to describe agro-morphological traits over a two-year study at four locations. Changes in grain yield, test weight, and plant height were related to differences in growing seasons, locations, genotypes, and their interactions. Thus, some genotypes are suitable for one location but not for another. However, a PCA showed that genotypes 2, 26, 28, 32, and 31 were the most stable across environments. In the 2022/2023 season, a negative relationship was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The time of ear emergence of wheat varieties was a variable where mean value showed late maturity to very late maturity in wheat varieties. It is known that plant height and heading date (in the current research evaluated as time of emergence) are adaptive traits, which means that the optimum plant height and heading date depend on the target environment [2]. The most frequent were varieties with short to medium plant length.…”
Section: Flag Leaf and The Whole Plants Characteristicsmentioning
confidence: 80%
See 2 more Smart Citations
“…The time of ear emergence of wheat varieties was a variable where mean value showed late maturity to very late maturity in wheat varieties. It is known that plant height and heading date (in the current research evaluated as time of emergence) are adaptive traits, which means that the optimum plant height and heading date depend on the target environment [2]. The most frequent were varieties with short to medium plant length.…”
Section: Flag Leaf and The Whole Plants Characteristicsmentioning
confidence: 80%
“…According to Hyles et al [8], wheat adaptation could be achieved through variation in phenology (seasonal timing of the lifecycle) and related traits (e.g., those affecting plant architecture). Nevertheless, the phenological expression of wheat plants is impacted by the environment and genetics, thus allowing wheat genotypes to achieve optimum productivity in Agriculture 2024, 14, 551 2 of 13 the environment in which they were primarily created [2]. In the same research it was also reported that environmental effects (E) explained approximately 72.2% of the total variation, whereas genotype (G) and GE interactions explained 6.9 and 18.3%, respectively.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation